Scutellarin protects cortical neurons against neonatal hypoxic‐ischemic encephalopathy injury via upregulation of vascular endothelial growth factor - Yu Zou; Chang‐Le Fang; Ya‐Ting Wang; Hua Li; Xi‐Liang Guo (Ibrain, 2022)
Abstract Neonatal hypoxic‐ischemic encephalopathy (NHIE) causes devastating cerebral damage and neurological deficits that seldom have effective therapies. This study aimed to explore the mechanisms underlying the therapeutic efficacy of Scutellarin in NHIE. NHIE models were successfully established. Zea‐longa score and triphenyte‐trazoliumchloride (TTC) staining demonstrated that hypoxia and ischemia (HI) insult induced prominent neurological dysfunctions and brain infarction. Protein microarray was applied to detect the differentially expressed genes in the cortex, hippocampus, and lung tissues of HI rats, which revealed the downregulation of vascular endothelial growth factor (VEGF) in these tissues. Additionally, double immunostaining uncovered VEGF expression was localized in the neurons. Besides, VEGF was decreasingly expressed in oxygen‐glucose deprivation (OGD) neurons, which was intriguingly reversed by Scutellarin treatment. Moreover, VEGF silencing increased OGD‐induced neuronal apoptosis and attenuated neurite outgrowth, which was enhanced by Scutellarin administration. GeneMANIA predicted a close correlation of VEGF with caspase 3, caspase 7, and interleukin (IL)‐1β, and qRT‐PCR revealed that Scutellarin treatment depressed the expression levels of them elevated in OGD neurons, but the Scutellarin‐depressed levels of these factors were prominently increased after VEGF silencing. Our findings suggested that Scutellarin exerted neuroprotective effects in NHIE potentially through mediating VEGF‐targeted inactivation of caspase 3, caspase 7, and IL‐1β.